PLANNING CONCEPT OF RISK MANAGEMENT IN CONSTRUCTION PROJECT - Nafaa Alfaitouri faraj Nasr; Pratikso .; Prabowo Setiyawan (Prosiding Seminar Nasional Inovasi Dalam Pengembangan SmartCity, 2017)
Construction project has many risks; therefore it should be managed correctly and implemented from start to finish. Risk management is the correct way to minimize the risk in construction project. In the context of managing risk, people in construction company can analyze the risk that may happened with SWOT analysis as a tool to observe and determine strategy.Keyword: SWOT analysis, risk management, construction project